PENGARUH PEMBELAJARAN COOPERATIF TIPE MAKE A MATCH DAN PEMBELAJARAN KONVENSIONAL TERHADAP HASIL BELAJAR PKn DITINJAU DARI KEMANDIRIAN BELAJAR SISWA PADA MTs N DI KABUPATEN KUDUS - SUSANTY, ELLA (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
The aims of this research are : (1) to find whether there is the presence or absence of differences influence of learning achievement between students taught by the Make A Match method and students taught by conventional methods and to determine which groups of students are better, (2) whether there is any influence difference of learning achievement between students who have a high independent learning and students who have a low independent learning. And to determine which groups of students are better. (3) to find whether there is the presence or absence of an interaction influence between learning methods and independent learning in relation to student achievement. This is an experimental research. Its population is the students of eight grade of MTs N Kudus. Methods of data collection in this research used the documentation and test methods. Analysis of data used two- way analysis of variance. Based on the analysis and discussion of hypothesis testing can be concluded that: (1) there are significant differences in learning outcomes of Civics Lesson in groups used the Make a Match and conventional methods. Student learning outcomes in Civics lesson with Make a Match method is better than the students who used conventional methods. (2) There are significant differences in the Civics learning outcomes of students with igh independent learning and groups of students with low independent learning. Student learning outcomes in Civics lesson who had a high independent learning better than the students who have a low independent learning. (3) There is interaction betweenlearning method and independent learning towards Civics learning outcomes. Learning achievement in civics lesson in group of Make a Match method with high independent learning had the highest average value, while the conventional method with low independent learning has the lowest average value. The research suggests that it is important for the students to improve their independent learning and a teacher should be able to determine the appropriate learning method for his lesson. A principal should encourage the teachers to improve their teaching competency in choosing teaching methods in the classroom and to conduct other research in related methods of teaching. Keywords: Cooperative Learning Model of Make A Match Type, Conventional, Learning Outcomes